"I'm Meltiiiiiing…": The Decline of Response Rates and the Impact of Nonresponse Bias on the Results of National Surveys at Small Colleges. Issue 173 (July 2017) - Lin, Wei‐Fang; Hewitt, Gordon J.; Videras, Julio
Abstract : This chapter examines the impact of declining student response rates on surveys administered at small‐ and medium‐sized institutions. The potential for nonresponse bias and its effects are addressed.